Jenis, Sebab, dan Dampak Multilingualisme Masyarakat Balikpapan - Annisa, Luthf (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2023)
This research aims to determine the type of multilingualism in Balikpapan society along with its causes and impacts. This research is qualitative. obtaining the data from 27 participants and interviews with 3 informants. Data collection was carried out through questionnaires. Data analysis was carried out by analyzing questionnaire results and analysis results in the form of componential analysis and cultural themes. The results of the research show that the multilingualism abilities possessed by the community are dominant and passive responsive multilingualism, meaning that the community is more proficient in one language than another and has the ability to understand various languages but is less able to speak these languages. The three main causes of multilingualism in Balikpapan society are the community environment, independent learning, and transmission from parents. From the multilingualism of Balikpapan society, the phenomenon of code mixing emerged. The people of Balikpapan mix one language with another. === Penelitian ini bertujuan untuk mengetahui jenis multilingualisme masyarakat di Balikpapan beserta sebab dan dampaknya. Penelitian ini merupakan penelitian kualitatif. Data dalam penelitian ini diperoleh dari 27 partisipan dan wawancara dengan 3 informan Pengumpulan data dilakukan melalui kuisioner. Analisis data dilakukan dengan menganalisa hasil angket dan hasil wawancara dalam bentuk analisis komponensial dan analisis tema budaya. Hasil penelitian menunjukkan bahwa Kemampuan multilingualisme yang dimiliki masyarakat adalah multilingualisme dominan dan pasif responsif artinya masyarakat lebih menguasai satu bahasa daripada bahasa lain dan memiliki kemampuan dalam memahami berbagai bahasa namun kurang dalam berbicara bahasa-bahasa tersebut. Adapun tiga penyebab utama kemampuan multilingualisme di masyarakat Balikpapan adalah lingkungan masyarakat, pembelajaran mandiri, dan transmisi dari orang tua. Dari multilingualisme masyarakat Balikpapan ini muncul fenomena campur kode. Masyarakat Balikpapan mencampurkan bahasa satu dengan bahasa lain.